Microwave irradiated copolymerization of xanthan gum with acrylamide for colonic drug delivery - Jaafar, Hawa; Anjum, Fozia; Bukhari, Shazia Anwer; Siddique, Muhammad; Shahid, Muhammad; Potgieter, J. Herman; Ercisli, Sezai; Zia-Ul-Haq, Muhammad (Elsevier, 2015)
Xanthan gum (XG) is a polysaccharide produced by Xanthomonas campestris. The aim of the present study was to modify the xanthan by hydrolysis and grafting with acrylamide through microwave irradiation for different time intervals. Pure xanthan was partially hydrolyzed via enzymatic and chemical treatments followed by optional grafting. Proximate composition analysis, moisture content, and carbohydrate, protein, lipid, and fiber contents were determined. The morphological characteristics, structural composition, functional groups, and heat resistance of the crude, hydrolyzed, and grafted gum were evaluated using SEM, XRD, FTIR spectroscopy, and TGA. Morphological studies revealed that xanthan was broken down into smaller fragments as a result of hydrolysis and became somewhat smoother. Thermal analysis studies indicated a larger heat tolerance in the grafted xanthan relative to that of the native and hydrolyzed gums. Xanthan bound to a triamcinolone drug was evaluated in the context of controlled drug release. Controlled drug release correlated well with the exposure time to microwaves used to graft the gum.